2023
DOI: 10.1002/ame2.12350
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing diabetic kidney disease animal models: Insights from a meta‐analytic approach

Fanghong Li,
Zhi Ma,
Yajie Cai
et al.

Abstract: Diabetic kidney disease (DKD) is a prevalent complication of diabetes, often leading to end‐stage renal disease. Animal models have been widely used to study the pathogenesis of DKD and evaluate potential therapies. However, current animal models often fail to fully capture the pathological characteristics of renal injury observed in clinical patients with DKD. Additionally, modeling DKD is often a time‐consuming, costly, and labor‐intensive process. The current review aims to summarize modeling strategies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…Circular RNAs (circRNAs) are a special kind of noncoding RNA with a closed loop structure and extremely stable expression (10)(11)(12). The important regulatory effect of circRNA on cell biological functions in human disease has been confirmed (13)(14)(15)(16). For example, it was found that circ-HIPK2 could promote myocardial oxidative injury by increasing cell apoptosis and autophagy (17).…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a special kind of noncoding RNA with a closed loop structure and extremely stable expression (10)(11)(12). The important regulatory effect of circRNA on cell biological functions in human disease has been confirmed (13)(14)(15)(16). For example, it was found that circ-HIPK2 could promote myocardial oxidative injury by increasing cell apoptosis and autophagy (17).…”
Section: Introductionmentioning
confidence: 99%